(untitled) (Research, Society and Development, 2023)
The literature, in recent years, has been demonstrating that there is a relationship between hearing loss and the cognitive performance of the elderly, with cognitive decline. The current paper proposes to analyze the cognitive performance in elderly people with hearing loss, users and non-users of the Hearing Aid (HA). Participated in this survey eighty elderly diagnosed with hearing loss and socioeconomic problems. This study was a quantitative, cross-transversal and observation study. Who were submitted to two assessment instruments: 1) sociodemographic characterization questionnaire; 2) Montreal Cognitive Assessment. For data analysis were used descriptive analysis, additionally Student’s T, for correlation of variables, Pearson’s Correlation Coefficient test and for comparison of the proportions of variables, Pearson’s chi-square test. The results showed that elderly people with hearing loss, users of HA and a higher level of education, had better performance in the cognitive test. The research findings will assist health professionals in the assessment and cognitive monitoring of elderly people with hearing loss, as well as how the use of HA contributes to the positive effects on cognition.